Community-Based Social Learning in Religious Transformation: A Study of the Wetu Telu–Waktu Lima Transition in Lombok, Indonesia - Herman Zuhdi; Febi Laeli Putri (CV. Yazri Aksara Nusantara, 2026)
The transition from Wetu Telu to Waktu Lima among the Sasak community in Lombok reflects a significant process of religious and social transformation involving changes in religious practices, knowledge systems, and cultural identities. This study investigates the role of community-based social learning in shaping and facilitating this transformation. A qualitative case study approach was employed in North Lombok using in-depth interviews, observation, document analysis, and oral history. Data were analyzed through thematic analysis to identify patterns of learning, interaction, and adaptation within the community. The findings indicate that Wetu Telu functioned as a traditional social learning system through which religious and cultural values were transmitted across generations. The transition toward Waktu Lima was supported by religious leaders, families, Islamic educational institutions, and community organizations through processes of observation, participation, dialogue, and social interaction. These mechanisms enabled the community to adopt new religious orientations while maintaining important elements of local cultural identity. The study highlights community-based social learning as a key mechanism in religious transformation.Transisi dari Wetu Telu menuju Waktu Lima pada masyarakat Sasak di Lombok merupakan proses transformasi sosial dan keagamaan yang ditandai oleh perubahan praktik keagamaan, sistem pengetahuan, dan identitas budaya. Penelitian ini bertujuan menganalisis peran pembelajaran sosial berbasis komunitas dalam mendorong dan memfasilitasi proses transformasi tersebut. Penelitian menggunakan pendekatan studi kasus kualitatif yang dilakukan di Lombok Utara melalui wawancara mendalam, observasi, dokumentasi, dan sejarah lisan. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi pola pembelajaran, interaksi, dan adaptasi yang berkembang dalam komunitas. Hasil penelitian menunjukkan bahwa Wetu Telu berfungsi sebagai sistem pembelajaran sosial tradisional yang mentransmisikan nilai-nilai keagamaan dan budaya antargenerasi. Transisi menuju Waktu Lima didukung oleh tokoh agama, keluarga, lembaga pendidikan Islam, dan organisasi masyarakat melalui proses observasi, partisipasi, dialog, dan interaksi sosial. Mekanisme tersebut memungkinkan masyarakat mengadopsi orientasi keagamaan baru tanpa kehilangan unsur-unsur penting identitas budaya lokal. Penelitian ini menegaskan pentingnya pembelajaran sosial berbasis komunitas dalam menjelaskan transformasi keagamaan